O papel das plataformas de redes sociais na subversão do conceito de comunidade virtual: elementos para a compreensão da construção da subjetividade contemporânea - Oliveira, Thaís (2023)
This research aims to analyze the forms of collective relationships in contemporary society through social media platforms. Over the years, virtual communities have sparked great interest among researchers and sociologists since the emergence of the first social interaction platforms in the second half of the 1980s. In this study, we seek to revisit crucial moments in the history of virtual communities and examine the transformations of platforms with the support of social networks. We will utilize a sociological approach to delimit the possibilities of understanding the concept of "community." In this research, we will examine the main platforms of social interaction, such as The Well and Instagram, classifying and analyzing their characteristics, tools, and functionalities adapted to the current context. We will employ Granovetter's theory of "weak ties" (1974-1983) to comprehend the importance of expanding the repertoire of interactions and enabling mobility between diverse social groups. Recuero (2009) and Rogério da Costa (2004) also contribute to the understanding of social capital and its influence on online social interactions. This study also highlights the impact of neoliberalism, discourses of success, and the construction of self-centered narratives. Authors Illouz (2011) and Sibilia (2016) observe how self-representation in digital profiles relates to the construction of online identities. Hardt and Negri (2005-2018) are also important references in addressing the relationship between crowds and individual profiles. Through this research, it is possible to comprehend the dynamics of interaction supported by virtual communities and the transformations of social media platforms, considering the relationship between the digital profile and the other. This analysis contributes to a broader reflection on the role of social media in contemporary society and the challenges faced in the face of uncontrollable subjectivity production